Application of Bandura's Theory to Breastfeeding Self-Efficacy of Mothers in the Working Area of Dahlia Health Center, Makassar City - Ayatullah Harun; Ruqaiyah; Noviyani Hartuti; Fatmawati Amir; Basmalah Harun (Jurnal Penelitian Pendidikan IPA, 2025)
This study investigated breastfeeding self-efficacy (BSE) among mothers attending the Dahlia Health Center in Makassar City, Indonesia, where exclusive breastfeeding rates were reported at 73.97% in 2023. Guided by Bandura’s theory of self-efficacy, a cross-sectional design was employed to simultaneously assess various factors influencing BSE. The targeted participants included 38 breastfeeding mothers, selected based on specific criteria. Data were collected through structured questionnaires, focusing on mothers’ confidence levels regarding breastfeeding. Trained enumerators conducted direct interviews ensuring informed consent. Statistical analysis, utilizing methods such as linear regression and correlation, revealed that 76.3% of respondents exhibited good BSE. Significant relationships were identified between key factors: breastfeeding experience (p = 0.043), observation of others (p = 0.000), and verbal persuasion (p = 0.01). Additionally, the mother's physical and emotional health also significantly influenced BSE (p = 0.00). The findings highlight the importance of positive experiences, social support, and maternal health in enhancing confidence in breastfeeding. Recommendations include developing training programs for health workers aimed at providing emotional support and involving family members in delivering consistent verbal encouragement to breastfeeding mothers. This approach may improve BSE and ultimately increase exclusive breastfeeding rates in the region.